2016
DOI: 10.5194/os-12-937-2016
|View full text |Cite
|
Sign up to set email alerts
|

Aragonite saturation states and pH in western Norwegian fjords: seasonal cycles and controlling factors, 2005–2009

Abstract: Abstract. The uptake of anthropogenic carbon dioxide (CO2) by the ocean leads to a process known as ocean acidification (OA), which lowers the aragonite saturation state (ΩAr) and pH, and this is poorly documented in coastal environments including fjords due to lack of appropriate observations.Here we use weekly underway data from the Voluntary Observing Ships (VOS) program covering the period 2005–2009 combined with data from research cruises to estimate ΩAr and pH values in several adjacent western Norwegian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
(56 reference statements)
6
20
0
Order By: Relevance
“…The seasonal changes in DIC and TA are the most important drivers for changes in Ω ar whereas the effects of variations of SST and SSS (not shown) on Ω ar are negligible. This is in agreement with Omar et al (), who analyzed data from the southwestern Norwegian coast using a different method and concluded that seasonal changes in DIC and TA are the most important drivers for changes in Ω ar , and variations of SST and SSS are less relevant. Again, we note that the TA influence is enhanced in the Skagerrak region compared to the NAW region.…”
Section: Resultssupporting
confidence: 91%
“…The seasonal changes in DIC and TA are the most important drivers for changes in Ω ar whereas the effects of variations of SST and SSS (not shown) on Ω ar are negligible. This is in agreement with Omar et al (), who analyzed data from the southwestern Norwegian coast using a different method and concluded that seasonal changes in DIC and TA are the most important drivers for changes in Ω ar , and variations of SST and SSS are less relevant. Again, we note that the TA influence is enhanced in the Skagerrak region compared to the NAW region.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have shown that SAMI‐pH and SAMI‐CO 2 sensors are stable over a time period of several months, showing no significant drift during a deployment period (Omar et al, ), although the p CO 2 sensors require in situ validation during deployment (Cullison‐Gray et al, ; DeGrandpre et al, ). The differences between discrete and sample p CO 2 and pH, along with the comparison of in situ and calculated values, are shown and discussed below.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, and most importantly, they also found that at all sites T, DIC, and TA are the principal drivers of seasonal pH variability. Omar et al [2016] studied seasonal cycles of pH in western Norway fjords and found that the combined effect of T and TA changes virtually compensates for the opposing effect of DIC changes on seasonal pH variability. Figure 2 shows the quantitative contributions of changes in T, DIC, and TA on pH seasonality for two sites in the Southern Ocean (Drake Passage areas 1 and 4), the Iceland Sea station, DYFAMED, Bermuda Atlantic Time-series Study (BATS), European Station for Time series in the Ocean Canary Islands (ESTOC), and Station ALOHA.…”
Section: Latitudinal Trends In Factors Driving Seasonality In Phmentioning
confidence: 99%